Pengaruh Promosi Penjualan dan Kualitas Produk terhadap Minat Beli Konsumen di Alfamart Kabupaten Purwakarta - Rahayu, Riska Sri; Nurfrasetia, Nadya Ayu; Kahuripan, Muhammad Bintang; Basuki Putri, Pandena Kicky (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the effect of sales promotion and product quality on consumer purchasing interest at Alfamart Purwakarta Regency. In a competitive business world, promotional strategies and product quality are two important factors in attracting attention and maintaining consumer loyalty. The method used in this study is a quantitative approach with multiple linear regression analysis, which measures the relationship between independent variables (sales promotion and product quality) and dependent variables (consumer purchasing interest). The results of the study indicate that sales promotion and product quality have a positive and significant effect simultaneously and partially on consumer purchasing interest. In addition, an interaction was found between promotion and product quality which resulted in a synergistic effect in increasing purchasing interest. These findings contribute to companies in designing more effective marketing strategies to increase sales and customer satisfaction.